Exercise Induced-Cytokines Response in Marathon Runners: Role of ACE I/D and BDKRB2 +9/-9 Polymorphisms - Sierra, Ana Paula Renno; Martínez Galán, Bryan Steve; de Sousa, Cesar Augustus Zocoler; de Menezes, Duane Cardoso; Branquinho, Jéssica Laís de Oliveira; Neves, Raquel Leão; Arata, Júlia Galanakis; Bittencourt, Clarissa Azevedo; Barbeiro, Hermes Vieira; de Souza, Heraldo Possolo; Pesquero, João Bosco; Cury-Boaventura, Maria Fernanda (Frontiers in Physiology, 2022)
Renin-angiotensin system (RAS) and kallikrein-kinin system (KKS) have a different site of interaction and modulate vascular tone and inflammatory response as well on exercise adaptation, which is modulated by exercise-induced cytokines. The aim of the study was to evaluate the role of ACE I/D and BDKRB2 +9/−9 polymorphism on exercise-induced cytokine response. Seventy-four male marathon finishers, aged 30 to 55 years, participated in this study. Plasma levels of exercise-induced cytokines were determined 24 h before, immediately after, and 24 h and 72 h after the São Paulo International Marathon. Plasma concentrations of MCP-1, IL-6 and FGF-21 increased after marathon in all genotypes of BDKRB2. IL-10, FSTL and BDNF increased significantly after marathon in the genotypes with the presence of the −9 allele. FSTL and BDNF concentrations were higher in the −9/−9 genotype compared to the +9/+9 genotype before (p = 0.006) and after the race (p = 0.023), respectively. Apelin, IL-15, musclin and myostatin concentrations were significantly reduced after the race only in the presence of −9 allele. Marathon increased plasma concentrations of MCP1, IL-6, BDNF and FGF-21 in all genotypes of ACE I/D polymorphism. Plasma concentrations of IL-8 and MIP-1alpha before the race (p = 0.015 and p = 0.031, respectively), of MIP-1alpha and IL-10 after the race (p = 0.033 and p = 0.047, respectively) and VEGF 72 h after the race (p = 0.018) were lower in II homozygotes compared to runners with the presence of D allele. One day after the race we also observed lower levels of MIP-1alpha in runners with II homozygotes compared to DD homozygotes (p = 0.026). Before the marathon race myostatin concentrations were higher in DD compared to II genotypes (p = 0.009). Myostatin, musclin, IL-15, IL-6 and apelin levels decreased after race in genotypes with the presence of D allele. After the race ACE activity was negatively correlated with MCP1 (r = −56, p < 0.016) and positively correlated with IL-8, IL-10 and MIP1-alpha (r = 0.72, p < 0.0007, r = 0.72, p < 0.0007, r = 0.47, p < 0.048, respectively). The runners with the −9/−9 genotype have greater response in exercise-induced cytokines related to muscle repair and cardioprotection indicating that BDKRB2 participate on exercise adaptations and runners with DD genotype have greater inflammatory response as well as ACE activity was positively correlated with inflammatory mediators. DD homozygotes also had higher myostatin levels which modulates protein homeostasis.